The use of isotretinoin in low doses and unconventional treatment regimens in different types of acne: a literature review - Torzecka, Jolanta D.; Dziankowska-Bartkowiak, Bożena; Gerlicz-Kowalczuk, Zofia; Wozniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
High effectiveness of isotretinoin treatment for severe types of acne resistant to antibiotics has been widely recognized. However, the recommended doses in conventional therapy, according to consensus of the Polish Dermatological Society, may cause serious adverse effects. Thus, research into less stressful, alternative treatment regimens with the use of low doses of isotretinoin has been carried out. The aim of the paper was to review the selected papers where authors present the results of their studies on different regimens with the use of isotretinoin in low doses in patients with acne, evaluate their efficacy, patient satisfaction, frequency of adverse effects, recurrences and also treatment costs.